HUBUNGAN SIKAP PENGENDALIAN DIRI DALAM PENGGUNAAN MEDIA JEJARING SOSIAL FACEBOOK DENGAN PERILAKU SEKSUAL PRANIKAH REMAJA USIA 15–19 TAHUN (STUDI DI KELURAHAN KAPASMADYA BARU KECAMATAN TAMBAKSARI KOTA SURABAYA) - Annisa Sabila Novandra; Nunik Puspitasari (The Indonesian Journal of Public Health, 2017)
Facebook is widely used in social communication, especially adolescents. Facebook can be easily accessed by using their smartphone. One of negative effect from facebook is unhealthy pre-marital sexual behavior. This effect can be minimized if the adolescents has a good self-control. This study was analyticobservational with cross-sectional design. The goal was analyze correlation between self-control of using facebook and pre-marital sexual behaviour. Self-control variable in this study foccused on accepting a friend request from someone who is never known, communicating with someone who is never known on facebook, asking to meet each other in real life with someone who is never known on facebook, and accepting to meet each other in real life with someone who is never known on facebook. The population was 13.532 adolescents (15–19 years old) who was living at Kapasmadya Baru, Tambaksari, Surabaya City, Indonesia in 2016. Sampling was simple random sampling and obtained 97 sample. The analysis used Chi-square test with α = 5%. The result showed that all of adolescents communicate easily with someone who is never known before. There were correlation between self-control of using facebook and pre-marital sexual behaviour (p = 0.000). So that, adolescents need support from their social living, especially their parents to control themselves during use facebook or another social media.Keywords: self-control, facebook, adolescent, pre-marital sexual behaviour